Developing Entrepreneurial Skills for Vulnerable Students in Pattani - Chanarnupap, Sansanee; Nuanjunkong, Nilubol; Vanichanon, Arunrut; Saetae, Rungthip; Poonsin, Tanchanok; Jansoon, Ninna (Parichart Journal, 2024)
This research article aimed to develop entrepreneurial skills of vulnerable students by means of action research. The study site was one of the ragged schools in Pattani Province. The Sample group was a total of 30 secondary school students which was selected by a purposive sampling method. The process of entrepreneurial skills development was adhered to the action research spiral which was comprised of 4 stages: 1. plan 2. act 3. observe, and 4. reflect. Duration of the study was 12 months (May 2022 - May 2023). The measurement and evaluation of the entrepreneurial skill development was done at the end of developmental process, by using competency assessment forms. The results exhibited that the student’s capability for all three dimensions was at good level. The average scores for entrepreneurial attribute, knowledge, and skill were 3.65 (from the full score of 5), 12.93 (from the full score of 20), and 32.50 (from the full score of 42), respectively. Our research results illustrated that even with low socioeconomic status and low background academic performance, these vulnerable students had potential to be developed for higher learning and entrepreneurial competency. A teacher was arguably a desirable change agent in driving that student’ development in learning and entrepreneurial ability. Concerning the country’s situation on poverty and inequality at the present time, entrepreneurship education, particularly for vulnerable students, could be proposed as a policy for the reduction of generational poverty.